Radial growth response to long-term thinning strategies in Nothofagus pumilio forests of Tierra del Fuego = Respuesta del crecimiento radial a estrategias de raleo de largo plazo en bosques de Nothofagus pumilio de Tierra del Fuego - Rodríguez‑Souilla, Julián (2023)
New silvicultural proposals based on long-term trials are needed to develop forest management strategies. Radial growth response was the preferred proxy for managers to define thinning levels and best years for intervention. We analyzed long-term thinning strategies in secondary Nothofagus pumilio forests (55 years old) in Tierra del Fuego (Argentina) to determine and quantify the effect on radial growth. Samplings were conducted in a trial area established in 1965 where three interventions (17, 33 and 44 years after harvesting) with different thinning strategies were applied. We employed dendrochronological techniques to measure and co-date ring widths, comparing 19 different thinning strategies (n = 100 slices x 2 reading sections). Average ring width (RW), basal area increment (BAI), and periodic annual increment every five years (PAI5) were calculated and compared through univariate comparisons. Radial growth responses were directly related to thinning intensity; however, a differential response was found according to thinning strategy (e.g. selective and systematic cuttings) and always significantly higher than the control (3 vs. 1 mm year-1). The maximum growth occurred between 2 and 4 years after thinning (YAT), and progressively decreased until reaching pre-cutting levels (5 to 8 YAT). The analyses of the thinning strategies showed that initial systematic thinning followed by at least light thinning when growth rates recover their pre-intervention values is the most convenient combination of intermediate treatments for Nothofagus pumilio forests. These results can contribute to better silvicultural decision-making in secondary forests and provide information to analyze the feasibility of their implementation.